1973
DOI: 10.1111/j.1432-1033.1973.tb02734.x
|View full text |Cite
|
Sign up to set email alerts
|

Diacetyl (Acetoin) Reductase from Aerobacter aerogenes

Abstract: The kinetics of the reversible reduction of acetoin and NADH to 2,3-butanediol andNAD by diacetyl (acetoin) reductase from Aerobacter aerogenes, have been investigated at pH 7.0, 5.8, and 4.8. The reaction follows an ordered bi-bi mechanism.Acetate acts as an inhibitor of the enzyme with respect to the substrate 2,3-butanediol. This inhibition increases for decreasing pH, indicating that it is acetic acid that is the effector.These results, in combination with earlier observations, show that high acetate conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

1981
1981
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…As a fermentation product, 2,3‐butanediol has long been produced by distillation (Larson and Stormer, 1973; Magee and Kosaric, 1987; Garg and Jain, 1995; Lee, 1999; Jansen and Tsao, 2007). Because of the low concentration of 2,3‐butanediol in the fermentation broth, and the stronger hydrogen bonding interaction between water molecules, recovery of 2,3‐butanediol by distillation is a very energy‐intensive process (Neel and Huang, 1991; Shao and Huang, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…As a fermentation product, 2,3‐butanediol has long been produced by distillation (Larson and Stormer, 1973; Magee and Kosaric, 1987; Garg and Jain, 1995; Lee, 1999; Jansen and Tsao, 2007). Because of the low concentration of 2,3‐butanediol in the fermentation broth, and the stronger hydrogen bonding interaction between water molecules, recovery of 2,3‐butanediol by distillation is a very energy‐intensive process (Neel and Huang, 1991; Shao and Huang, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Lactate is the most abundant by-product that consumes carbon flux and NADH in K. pneumoniae and competes with 2,3-BD biosynthesis [9]. Reducing the lactate and acetate yield decreased the acidification rate of the media, which is not favorable to cell growth [9,27]. Previous studies have reported that lactate and acetate can effectively inhibit Klebsiella cell growth, thereby affecting 2,3-BD production [28][29][30].…”
Section: Discussionmentioning
confidence: 97%
“…The enzymatic characteristics of BDH purified from P. polymyxa ZJ-9 were compared with those of BDH from K. pneumoniae IAM 1063 [8], Klebsiella terrigena VTT-E-74023 [17], Aerobacter aerogenes 1033 [18], and Saccharomyces cerevisiae [19] ( Table 2). The BDH enzyme of P. polymyxa ZJ-9 differed from those of the other strains in terms of its molecular weight, subunits, and K m values for some substrates.…”
Section: Discussionmentioning
confidence: 99%